Increasing Frequency and Burden of Cerebral Artery Atherosclerosis in Korean Stroke Patients - Kim, Young Dae (Yonsei University College of Medicine, 2010)
PURPOSE: Koreans have been undergoing rapid lifestyle changes that may have an effect on patterns of cerebral artery atherosclerosis. This study was aimed at determining the frequency and distribution of atherosclerosis in the cerebral arteries and associated temporal changes over the past eight-year period among Korean stroke patients. MATERIALS AND METHODS: By using stroke registry data registered between April 1999 and March 2007, we investigated the presence, severity, and location of cerebral artery atherosclerosis as determined by angiographic findings. Their annual patterns and association with vascular risk factors were investigated. RESULTS: Of 1,955 patients, 1,517 patients (77.6%) demonstrated atherosclerosis in one or more arteries. A significantly increasing trend of atherosclerosis was observed during the past eight years, which was ascribed to an increase of combined extracranial (EC) and intracranial (IC) atherosclerosis. The number of atherosclerotic arteries increased as the number of risk factors increased. In the multivariate analysis, the year and vascular risk factors were independent predictors of the presence of atherosclerosis. CONCLUSION: We found that the atherosclerotic burden has been increasing for the past eight years in Korean stroke patients, particularly the combined EC and IC subtype. Lifestyle changes and increase in vascular risk factors may be contributing factors.